Ultrafine bubble water Pengaruhnya dalam Pematahan Dormansi Benih Padi - Iswara, Vidya; Setiawan, Asep; Palupi, Endah R.; Purwanto, Y. Aris (Jurnal Penelitian Pertanian Tanaman Pangan, 2018)
The method for dormancy breaking could be developed by the usefull of nano bubbles technology, like ultrafine bubble water (UFB). The research aims to identify the effectivity of UFB water for dormancy breaking of rice seed. This research was arranged in a Completely Randomyzed Design with four replications and nine level treatments, i.e. control, aquadest, KNO3, UFB, and UFB 20 soaking for 24 and 48 hour, respectively. Rice seed without soaking showed the ABA content was 14.3%, aquadest, KNO3, UFB soaking for 24 hour about 10.1-11.5%, while for 48 hour about 8.9-9.9%. The maximum growth potential (MGP), more than 80% was obtained on dormancy breaking by KNO3, UFB, and UFB20 soaking for 48 hour, and UFB20 soaking for 24 hour. Aquadest soaking showed there is a increasing of MGP (less than 60%), however did not significant, as well as by 24 or 48 hour. KNO3 soaking, its dormancy breaking showed the MGP less than 80%, if the soaking less than 48 hour. The chemical scarification for dormancy breaking by KNO3, UFB, and UFB20 for 48 hour showed the radicle emergence more than 80%. The lowest radicle emergence was obtained on aquadest soaking for 24 hour, and followed by without soaking, KNO3 soaking, UFB soaking, and UFB20 soaking for 24 hour.